Evaluation of absorbable composite polylactide–hydroxyapatite bone fixation devices: a cohort study. (October 2016) - Ding, Jianxun; Zhuang, Xiuli; Chen, Xuesi
Abstract: Background: At present, most bone fixation devices are made of metal, and are applied to prevent the postoperative dislocation of bone fragments. The major issues with such metal bone fixation devices are the necessity for secondary surgery to remove the devices, stress shielding of bone, stimulation and erosion of bone and soft tissue, and limited biocompatibility. To mitigate these problems, we aimed to assess use of a flexible absorbable polymer bone fixation devices. These devices were certified for use in China in September, 2015. Methods: In this study, patients were treated at the First Hospital of Jilin University with absorbable fixation screws for fixation of non-weight-bearing bones (eg, metacarpal, phalange, talus, metatarsus, or inner ankle) or absorbable bone plates (eg, for hand, feet, ulna, or fibula fixation). Absorbable bone fixation devices were made from 90% by weight polylactide and 10% hydroxyapatite. Patients were followed up for at least 6 months, and evaluated clinically and radiographically at 3 months and 6 months after surgery. The ethics committee of the First Hospital of Jilin University gave ethical approval for the study and all patients provided written informed consent. Findings: Between February, 2011, and July, 2014, 45 patients (62 screws; 33 men, 12 women; mean age 41·7 years [range 19–63; SD 12·5]) had absorbable fixation screws implanted and 45 patients (45 bone plates; 35 men, ten women; mean age 39·2 years [range 24–60; SD 10·4]) had absorbable bone plates. The flexural strength of the tested bone screw was ≥170 MPa and flexural modulus was ≥4000 MPa, and those of bone plate were ≥100MPa and ≥3000 MPa. The high mechanical properties met the requirements of clinical applications. No patients required revision surgery, and no device-related adverse events were observed during the 6 month follow-up period. 6 months after implantation, the fracture healing rates were both 100% for both absorbable bone fixation screw and plate. Interpretation: Absorbable polylactide–hydroxyapatite bone fixation screws and plates seemed safe and effective in this study. Funding: National Natural Science Foundation of China (grants 51303174, 51473165, and 51390484 ).